Pharmacokinetics, efficacy, and safety of cannabidiol in dogs: an update of current knowledge - Di Salvo, Alessandra; Conti, Maria Beatrice; della Rocca, Giorgia (Frontiers in Veterinary Science, 2023)
In the last five years, interest has grown in using phytocannabinoids, particularly cannabidiol (CBD), in veterinary medicine to treat several pathologies, including pain, epilepsy, anxiety, nausea, anorexia, skin lesions, and even some types of cancer, among others. Indeed, due to a positive perception of CBD use, many pet owners are increasingly requesting this option to relieve their pets, and many veterinarians are exploring this possibility for their patients. Besides the widespread empiric use of CBD in pets, the research is trying to obtain proof of its efficacy and lack of adverse effects and to know its pharmacokinetics to define an appropriate posology. This review summarizes all data published so far about the canine pharmacokinetics, efficacy, and tolerability of CBD and cannabidiolic acid (CBDA). Despite a certain number of available pharmacokinetic studies, the kinetic profile of CBD has yet to be fully known, probably because of the very different experimental conditions. In terms of efficacy, most studies have tested CBD’ ability to relieve osteoarthritic pain. In contrast, few studies have evaluated its role in epilepsy, behavioral disorders, and skin lesions. From obtained results, some evidence exists supporting the beneficial role of CBD. Nevertheless, the limited number of published studies and the occurrence of bias in almost all require caution in interpreting findings. From tolerability studies, CBD’ side effects can be classified as mild or unremarkable. However, studies were prevalently focused on short- to medium-term treatment, while CBD is usually employed for long-term treatment. Further studies are warranted to define better whether CBD could be a valid adjunct in canine treatment.